Functional Foods - Amanda L. Ford; Wendy J. Dahl (EDIS)
A functional food is commonly defined as a food that provides benefits beyond the basic nutrition provided by that food. The additional benefit is due to a component in the food item that offers physical or biological benefits. As functional foods become increasingly popular in the U.S., it is important to be an informed shopper. This 3-page fact sheet was written by Amanda L. Ford and Wendy J. Dahl, and published by the UF Department of Food Science and Human Nutrition, November 2012.